CANINE EHRLICHIOSIS INDUCED MULTI-ORGAN DYSFUNCTION SYNDROME IN A LABRADOR RETRIEVER: A CASE REPORT - S.P. Abhijith`; H.J. Apoorva; A. Abdul Kalam; H.V. Sanjay; D. Chandrakumar; V.S. Lathamani; M.A. Kshama (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Canine monocytic ehrlichiosis is a tick-borne infectious disease of dogs caused by Ehrlichia canis, transmitted primarily through Rhipicephalus sanguineus. The disease typically progresses through acute, subclinical, and chronic stages, each characterized by distinct hematological and clinical alterations. A three-years-old male Labrador Retriever was presented to the Small Animal Medicine Unit, Veterinary College Hospital, Bengaluru, with a history of progressive anorexia, vomiting, and lethargy for the past seven days.Clinical examination revealed pallor of mucous membranes, multiple lymphadenopathies, mild dehydration, and tick infestation along with enlarged hepatic silhouette on abdominal palpation. Hematological analysis revealed normocytic normochromic non-regenerative anemia and thrombocytopenia, while serum biochemistry indicated markedly elevated alanine aminotransferase (ALT), aspartate aminotransferase (AST), and total bilirubin levels. Molecular confirmation by multiplex PCR detected genome of Ehrlichia canis, establishing a diagnosis of Canine Monocytic Ehrlichiosis. The dog was treated with inj. doxycycline @ 10 mg/kg IV q24h for three days followed by oral route along with supportive treatment. Initial improvement was observed; however, three weeks later, the dog developed azotemia and persistent elevation of BUN and creatinine, consistent with chronic kidney disease (CKD) secondary to multi-organ dysfunction syndrome (MODS).Therefore, early diagnosis combined with effective tick control remains essential, as advanced cases often carry a guarded prognosis despite appropriate antibiotic therapy.